Dystocia due to dizygotic twins in a crossbreed cow - a case report - Gitesh Saini; Manjeet Kataria (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Twining incidence is influenced by a wide variety of genetic and environmental factors ranging from 0.5 to 4%. This case report places on record the successful management of dystocia due to dizygotic twins in a pluriparous cross-breed cow of four and a half year of age in her third parity. Both fetuses were non identical and had separate placenta which suggest ‘Dizygotic twins’.